Septostomy during laser surgery for twin-to-twin transfusion syndrome - Andrei E. Bugerenko (IP Berlin A.V., 2021)
Aim. To assess the perinatal outcomes of monochorionic diamniotic (MCDA) pregnancy after fetoscopic laser coagulation of anastomoses (FLCA) performed for twin-to-twin transfusion syndrome (TTTS), accompanied by induced or unintentional septostomy, and to identify the factors leading to septostomy.